(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2023)
Innovative approaches often require collaboration between educators, administrators, and other stakeholders. However, silos and competing interests can make collaboration difficult. Schools can foster a culture of collaboration by creating opportunities for teachers and administrators to work together, sharing best practices, and encouraging cross-functional teams.